2004
DOI: 10.1029/2004gl020036
|View full text |Cite
|
Sign up to set email alerts
|

On the baroclinic structure of the Brazil Current–Intermediate Western Boundary Current system at 22°–23°S

Abstract: [1] The baroclinic structure of the Brazil Current(BC)-Intermediate Western Boundary Current (IWBC) at 22°-23°S was investigated. A reanalysis of the pioneer velocity profile measurements of the TRANSCOBRA Experiment [Evans and Signorini, 1985] revealed that the BC-IWBC system is about 75-80% baroclinic. Mapped velocity structure showed flow reversal at about 450 m, an IWBC thickness of 1200 m and core velocities exceeding 0.30 m s À1 . Total (baroclinic) transports for BC (southwestwards) and IWBC (northeastw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
97
0
48

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 11 publications
13
97
0
48
Order By: Relevance
“…1) as confirmed by their high CV's observed (Table I). This pattern has been observed before (13) and it is explained by the local topography interacting with the complex current flow and water mass structures (39). In distribution maps we identified nuclei of biological activity in the area of the reported São Tomé Eddy (23ºS, 40ºW; ref.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1) as confirmed by their high CV's observed (Table I). This pattern has been observed before (13) and it is explained by the local topography interacting with the complex current flow and water mass structures (39). In distribution maps we identified nuclei of biological activity in the area of the reported São Tomé Eddy (23ºS, 40ºW; ref.…”
Section: Discussionsupporting
confidence: 79%
“…4b) where they reached up to 85% of total abundance. The area south 19ºS is characterized by some oceanographic features as eddies and upwelings (13,39,43) that feed the epipelagic zone with cold and nutrient-rich waters remobilized from the bottom. This is the most probable explanation for the high nitrate values reported for station 1 and responsible for the dark spot on distribution map (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar deep undercurrents, although not seasonal, are found in other western-boundary-current systems. For instance, in the Brazil Current system, a deep undercurrent is located at 800 m (Da Silveira et al 2004), similar to the undercurrents of the Agulhas (Beal and Bryden 1997;Beal 2009) and East Australian (Mata et al 2000) current systems. In contrast to EBUs, alongshore winds in western-boundary current systems do not generate undercurrents (McCreary and Kundu 1985).…”
Section: Current Vertical Structurementioning
confidence: 99%
“…Silveira et al (2000) and Stramma et al (1990) observed it around 10 • S, and Soutelino (2008) The southward transport by the BC from the shore until 39 • W at 22 • S produced by the control run, the assimilation run and the HYCOM+NCODA in December 2009 were 1.3 Sv, 4.1 Sv and 4.8 Sv, respectively. According to Evans & Signorini (1985) and Silveira et al (2004), the BC transport in this region is given by 6 Sv and 5.6 ± 1.4 Sv, respectively. The northward transport by the IWBC in the same region were 7.89 Sv, 4.81 Sv and 1.92 Sv for the control run, the assimilation run and the HYCOM+NCODA, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…The northward transport by the IWBC in the same region were 7.89 Sv, 4.81 Sv and 1.92 Sv for the control run, the assimilation run and the HYCOM+NCODA, respectively. According to Silveira et al (2004) the observed transport by IWBC was 3.6 ± 0.8 Sv. Therefore, the assimilation run produced a positive impact in the currents and transport in this region not only in the surface but also in the subsurface.…”
Section: Resultsmentioning
confidence: 95%